A NEW CLINICAL DEFINITION OF EPILEPSY - T. V. Dokukina; M. V. Makhrov (Эпилепсия и пароксизмальные состояния, 2016)
Abstract: the article provides a revised definition of epilepsy, according to the recommendations of the International League Against Epilepsy. Epilepsy can be installed after one unprovoked seizure in people who have other factors associated with a high risk of permanent lowering of the threshold of convulsive readiness. Persons with reflex seizures also attributed to epilepsy. It is resolved that epilepsy is no longer for those who had no seizures for at least 10 years without antiepileptic therapy, provided that there are no known risk factors associated with a high risk of recurrence of seizures.